Effect of rotor–stator axial spacing on the pressure-rise performance and flow field in an axial pump. (September 2019) - Xu, Han; Jin, Donghai; Sun, Dakun; Du, Lin; Gui, Xingmin; Sun, Xiaofeng
In this paper, the effect of the rotor–stator axial spacing is investigated in an axial pump with the working fluid of water. The pressure-rise performance was tested at a range of flow rates. Results indicate that decreased axial spacing generates improved hydraulic head, especially when the flow rate is low. Particle image velocimetry measurement was performed and flow fields for five rotor phases were obtained in a low flow rate condition. Particle image velocimetry results demonstrate that the stator inlet flow is both affected by the wake of the rotor and the existence of the stator. As the axial spacing gets close, the incidence angle of the stator decreases and the flow separation on the suction side is restrained, and therefore the pressure rise ability is improved.